Athletic philistines? Edmond Warre and his Etonian sporting masters. Issue 2 (3rd April 2022) - Carter, Andy
ABSTRACT: Although athleticism arguably rescued English public schools from chaos in the early nineteenth-century, concerns were soon raised that too much attention was paid to sport at the expense of learning. Subsequently, the sporting philistine became thought of as a self-perpetuating type within public schools, with masters who cared for nothing but sport producing boys who thought likewise. Edmond Warre, who taught at Eton from 1860 to 1905, and was headmaster from 1884, is often cited as the leading example of this type, building up a group of sporting masters who made Eton a dominant force in sport, but achieving little else. However, this paper argues this view does Warre and his colleagues a disservice, and that his educational achievements were downplayed because of Eton's internal power struggles. While Eton, and other public schools, produced philistines aplenty, the best sportsmen were less likely to be among their ranks because they were increasingly motivated to study hard in order to qualify for university, and take advantage of the sporting opportunities offered there. Sporting and academic excellence were thus increasingly found in the same pupils, and sporting masters had a vested interest in providing their charges with the classical education required for Oxbridge entrance.